Decoupled early Holocene summer temperature and monsoon precipitation in southwest China. (1st August 2018) - Wu, Duo; Chen, Xuemei; Lv, Feiya; Brenner, Mark; Curtis, Jason; Zhou, Aifeng; Chen, Jianhui; Abbott, Mark; Yu, Junqing; Chen, Fahu
Abstract: Proxy-based reconstructions of Holocene temperature show that both the timing and magnitude of the thermal maximum varied substantially across different regions. Given the 'Holocene temperature conundrum', it is becoming increasingly important to reconstruct seasonal temperature variations. As a major component of the global monsoon system, the Indian summer monsoon (ISM) transports moisture and heat from the tropical oceans to higher latitudes and thus it has substantial socioeconomic implications for its regions of influences. We developed a well-dated, pollen-based summer temperature record (mean July; MJT) for the last 14, 000 years from Xingyun Lake in southwest China, where the climate is dominated by the ISM. MJT decreased during the Younger Dryas, increased slowly to high values during 8000–5500 yr BP, and decreased thereafter. The MJT record differs from that inferred using carbonate oxygen isotopes (δ 18 O) from the same sediment core. The latter record reflects variations in monsoon precipitation, with highest precipitation during the early Holocene (11, 000–6500 yr BP). We propose that summer temperature and precipitation in southwest China were decoupled during the early Holocene. Both MJT and monsoon precipitation decreased after the middle Holocene, tracking the trend in boreal summer insolation. We suggest that greater cloud cover, associated with high precipitation and generated by a strong summer monsoon, may have depressed early Holocene temperatures that would otherwise be driven by greater summer insolation. Melting ice sheets in high-latitude regions and high concentrations of atmospheric aerosols during the early Holocene may also have contributed, in part, to the relatively cool summer temperatures. Highlights: A well-dated and pollen-based Holocene mean July temperature (MJT) record is reconstructed from Xingyun Lake, southwestern China. The MJT record reveals a middle Holocene summer temperature maximum. δ 18 O record of authigenic calcite from the same core indicates that highest precipitation occurred during the early Holocene. Inner feedbacks including greater cloud cover, melting ice sheets and high concentrations of atmospheric aerosols may have caused decoupled variations of summer temperature and monsoon precipitation.